Pengaruh Kualitas Pelayanan Food and Beverage Department Terhadap Kepuasan Konsumen Hotel Daily Inn Jakarta - Herlina Herlina; Lila Muliani (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
This study aimed to analyze the effect of the food and beverage department service quality on customer satisfaction at the Daily Inn Hotel, Jakarta. This study used a quantitative method with a data collection technique in the form of questionnaires and literature studies. The population of this study was the consumers of the Daily Inn Hotel, Jakarta, that served by Food and Beverage Department during March 2019. The samples in this study were calcuated by Slovin Formula, with 10% error tolerance. The data then were processed by SPSS statistical analysis. The results of this study indicated that service quality had an effect on consumer satisfaction by 0.838 or 83.8% based on the coefficient of determination of 0.162 or 16.2% explained by other factors not included in this study. From the results of the T-test carried out, with the results of the analysis of 21.660 greater than 1.662 and a probability of 0.000 smaller than 0.60, it was concluded that H0 was rejected and H1 was accepted which means that the service quality variable (X) significantly affects the consumer satisfaction variable (Y).